Poezja życia / poezja instrukcji: poems Anrzeja Sosnowskiego w kontekście teorii poezji Ezry Pounda - Pietrzak, Wit (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
In the present article Andrzej Sosnowski’s poems is analysed against the theoretical principles elaborated by Ezra Pound. Pound’s postulates such as the ideogrammic method and the melo-, fano-, and logopoeia, all of which are briefly discussed, are used to characterise Sosnowski’s poetic practice. The article shows that, irreducible differences notwithstanding, both poets write in accordance with a set of similar principles. The difference between Sosnowski’s poems and Pound’s Cantos consists mainly in the fact that the former gives up on the inherently Poundian desire to reorganise reality in an epic work and seeks what may be termed a scene of voice on which one’s ownmost identity can be manifested. It is among the many discourses that comprise poems that a voice of life sounds in all its complexity and fragility.